2020
DOI: 10.1017/wet.2020.129
|View full text |Cite
|
Sign up to set email alerts
|

Effects of low-dose applications of 2,4-D and dicamba on cucumber and cantaloupe

Abstract: Agronomic crops engineered with resistance to 2,4-D or dicamba have been commercialized and widely adopted throughout the United States. Due to this, increased use of these herbicides in time and space has increased damage to sensitive crops. From 2014 to 2016, cucumber and cantaloupe studies were conducted in Tifton, GA to demonstrate how auxinic herbicides (2,4-D or dicamba), herbicide rate (1/75 or 1/250 field use), and application timing (26, 16, and 7 d before harvest (DBH) of cucumber; 54, 31, and 18 DBH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 24 publications
1
11
1
Order By: Relevance
“…The observed visual injuries for both commercial cultivars, ANA 334 and Cristel, in response to herbicide treatment at all three doses were ranked among the highest damage levels recorded by accessions, therefore, these cultivars were susceptible to all 2,4-D drift rates (Figures 1-3). In line with our findings, Hand et al [32] reported that by increasing the application rate of 2,4-D or dicamba from 1/25X to 1/7X their recommended field use rates (1120 and 560 g ae ha −1 , respectively), the level of visual injury in cantaloupe (Cucumis melo L.) increased up to 67%, 110%, and 100% at 18, 31, and 54 days before harvesting, respectively.…”
Section: Effect On Crop Injurysupporting
confidence: 92%
See 1 more Smart Citation
“…The observed visual injuries for both commercial cultivars, ANA 334 and Cristel, in response to herbicide treatment at all three doses were ranked among the highest damage levels recorded by accessions, therefore, these cultivars were susceptible to all 2,4-D drift rates (Figures 1-3). In line with our findings, Hand et al [32] reported that by increasing the application rate of 2,4-D or dicamba from 1/25X to 1/7X their recommended field use rates (1120 and 560 g ae ha −1 , respectively), the level of visual injury in cantaloupe (Cucumis melo L.) increased up to 67%, 110%, and 100% at 18, 31, and 54 days before harvesting, respectively.…”
Section: Effect On Crop Injurysupporting
confidence: 92%
“…Noticeably, after the application of 2,4-D at the drift rate of 208 g ae ha −1 , all crops significantly showed lower yield production than their untreated control plots [18]. By increasing the rate of 2,4-D from 44.8 to 160 g ae ha −1 , the cantaloupe fruit number and fruit weight reduced by 32% and 50%, respectively [32].…”
Section: Effect On Melon Fruit Yieldmentioning
confidence: 94%
“…Concentrations retained on the mulch were 1/50 to 1/100 the 1× rate of dicamba and 1/500 to 1/625 the 1× rate of 2,4-D. Previous studies have noted a high level of injury and yield loss from dicamba at much lower rates than those observed on the mulch in this study when applied to the foliage of squash and cantaloupe (Culpepper and Vance 2019;Dittmar et al 2016;Hand et al 2019). Injury from 2,4-D has not been noted from rates lower than 1/300× for either cantaloupe or squash (Culpepper and Vance 2019).…”
Section: Discussioncontrasting
confidence: 42%
“…However, Python cucumber demonstrated leaf deformation that increased rapidly from 1.00 to 1.30 g ae ha −1 , where it reached a maximum at 7% visual deformation (Figure 1A). In a study by Hand et al (2021) in which 1/250th of the labeled rate of dicamba (2.24 g ae ha −1 ) was applied, 'Impact' and 'Bristol' cucumbers visually evaluated 9 d after application demonstrated 10% visual injury on average, thereby demonstrating the possibility that sensitivity differences exist among cultivars of the same species.…”
Section: Cucurbitaceaementioning
confidence: 99%